Iron(III)–Quercetin Complex: In Vivo Acute Toxicity and Biodistribution of Novel MRI Agent - Innuan P; Kongkarnka S; Thongtharb A; Kantapan J; Dechsupa N (International Journal of Nanomedicine)
Phattarawadee Innuan,1,2 Sarawut Kongkarnka,3 Atigan Thongtharb,4 Jiraporn Kantapan,1,2 Nathupakorn Dechsupa1,2 1Molecular Imaging and Therapy Research Unit, Department of Radiologic Technology, Faculty of Associated Medical Sciences, Chiang Mai University, Chiang Mai, 50200, Thailand; 2Department of Radiologic Technology, Faculty of Associated Medical Sciences, Chiang Mai University, Chiang Mai, 50200, Thailand; 3Department of Pathology, Faculty of Medicine, Chiang Mai University, Chiang Mai, 50200, Thailand; 4Department of Companion Animal and Wildlife Clinic, Faculty of Veterinary Medicine, Chiang Mai University, Chiang Mai, 50100, ThailandCorrespondence: Nathupakorn Dechsupa; Jiraporn Kantapan, Molecular Imaging and Therapy Research Unit, Department of Radiologic Technology, Faculty of Associated Medical Sciences, Chiang Mai University, Chiang Mai, 50200, Thailand, Email nathupakorn.d@cmu.ac.th; Jiraporn.kan@cmu.ac.thBackground: The iron(III)–quercetin complex, known as “IronQ”, is an innovative MRI contrast agent composed of one Fe(III) ion and two quercetin molecules. IronQ is efficiently internalized by cells, enabling T1-weighted MRI tracking. It has demonstrated therapeutic benefits in reducing inflammation in an intracerebral hemorrhage (ICH) mouse model and offers a safer alternative to gadolinium-based agents by avoiding cytotoxicity and genotoxicity. These properties make IronQ a promising candidate for safe and effective MRI contrast enhancement.Purpose: This study aims to further the development of IronQ as an MRI contrast agent by investigating its biodistribution, pharmacokinetics, and acute toxicity in a preclinical animal model.Methods: The relaxivity of IronQ was measured in water and whole blood phantoms. Acute toxicity was evaluated in Sprague Dawley rats administered single intraperitoneal doses of IronQ (75, 150, and 225 μmol Fe/kg BW) over a 14-day period. Pharmacokinetic studies were performed at a dose of 150 μmol Fe/kg BW, with blood iron content analyzed using ICP-OES. For in vivo biodistribution, SD rats were administered an intravenous dose of IronQ (225 μmol Fe/kg BW), followed by MR imaging using a 1.5 T scanner and subsequent tissue-ICP analysis.Results: The longitudinal relaxivity (r1) of IronQ was measured to be 2.17 mm⁻¹s⁻¹ in ultrapure water and 3.56 mm⁻¹s⁻¹ in whole blood. Acute toxicity studies showed no mortality, morbidity, or significant biochemical changes, with histopathology confirming no irreversible organ damage. Pharmacokinetics revealed peak blood iron content at 1.1 hours post-administration and clearance within 24 hours. MRI demonstrated enhanced T1 signal intensity, particularly in the liver and kidney.Conclusion: These findings provide valuable insights into the safety, pharmacokinetics, and imaging efficacy of IronQ, highlighting its potential as a robust and biocompatible MRI contrast agent.Keywords: magnetic resonance imaging, contrast agent, in vivo toxicity, biodistribution, IronQ